Streaming Apps - A Study on Consumer Satisfaction Toward the Usage of These Platforms During COVID-19 in Kolkata, West Bengal - Chawla, Udit; Shaw, Jyoti; Choudhary, Sonam (Indian Journal of Marketing, 2022)
In todayâ€™s world, virtual streaming platforms are the primary source of entertainment. People gradually shift from traditional entertainment channels to online streaming platforms as they offer more improvised services. During the COVID-19 period, the streaming sector saw massive growth in the number of users. As a result, streaming platforms are now widely seen as the entertainment industryâ€™s future. From offering high-quality material to connecting individuals through various streaming platforms, OTT platforms have gained prominence recently, particularly during the pandemic. Purpose : To identify the factors influencing usersâ€™ satisfaction with a streaming platform in Kolkata, West Bengal, and to establish how these attributes and different streaming platforms are related. Methodology : Kolkata, West Bengal, was selected for the survey, and it was undertaken with the help of a structured questionnaire and casual interaction with the users. Findings : This study discovered that consumer satisfaction was primarily determined by two critical factors: â€œFringe Benefitsâ€ and â€œRefreshment.â€ The factor â€œFringe Benefitsâ€ was found to be substantially influential. In addition, usersâ€™ satisfaction could also correlate to the quality of services provided to the streaming platforms using correspondence analysis. Various online streaming platforms were discovered to be popular, delivering high-quality material with a wide range of alternatives, limited advertisements, and high-quality and extensive features at a reasonable price. Furthermore, we used cluster analysis to discover three clusters that influenced consumers of various ages when watching online on various streaming sites. These clusters were â€œGen Z Socializing,â€ â€œGen Y Entertaining,â€ and â€œGen X Quality Essence.â€